Fra Troia e la Tavola Rotonda: La vendetta dei discendenti di Ettore, pastiche tre-quattrocentesco (Bisanzio e l'Occidente, 2018)
The Vendetta dei discendenti di Ettore is an anonymous and quaint literary pastiche, stillunpublished, which blends the Trojan tradition with the Arthurian one. It was likelywritten between the end of the XIV and the beginning of the XV century, possibly inLucca, before the Croniche by Giovanni Sercambi, who seems to have drawn inspirationfrom it in some brief chapters. It stages a kind of world war that involves, more than athousand six hundred years after the fall of Troy, the descendants of Hector and the fatherof king Arthur, Uter Pendragon, joined by other knights of the Round Table andsupported by Romans and Persians in a mission to exact revenge on Greeks and the newGreeks (the Byzantines). The text, probably inspired by the Roman de Perceforest, andalways indebted to Wace’s Brut, singer of the translatio imperii, stages an epic clashbetween culture and nature, barbarism and civilization, employing a narrative rhythmsometimes unlikely and almost dreamlike, set in a kind of parallel universe rich incontradictions that can be interpreted using Matte Blanco’s bi-logic. These notablefeatures let us forget the humble literary quality of the text.
Keywords: Filologia romanza